PERGESERAN PARADIGMA SISTEM INFORMASI MANAJEMEN - Pramitha, Devi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Management Information Systems (MIS) is a field that began to develop since the 1960s. Although there is no single consensus, it is generally defined as a driver's license system that provides information used to support the operation, management, and decisionmaking in organization. Prainformasional in the community, the people in it using a rigid paradigm assisted by intuition, the basis used by them to select the types of information needed is often not obvious because it is colored by the subjective nature of perception. But then in today's modern society, in addition to the paradigm shift that uses a creativeapproach to merger, also using the scientific paradigm that enables the selection of information can be done quickly and accurately. In the world of education though, MIS become one of the important factors to improve services at the same time saving for education. With advances in the development of education in Indonesia, both from anadministrative or technological aspect, the process of education services in Indonesia should be done effectively and efficiently. Therefore, to develop the quality of education needed some support facilities, where one of the supporting facilities is the application of information technology in the field of Management Information SystemsKeywords: Management Information System, Paradigm Shift, Education